Rancang Bangun Layanan Pengaduan Wisata Berbasis Web Dengan Pendekatan UML Pada DINBUDPAR Rembang - Sholikhan, Ahmad Nur; Widayati, Yohana Tri; Galih, Sinta Tridian (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Rembang Regency has approximately 39 tourist attractions, where these tourist spots were found to have numerous visitors each month in 2023. This is crucial in boosting the country's foreign exchange earnings. However, public service management at the Rembang Regency Department of Culture and Tourism still employs conventional methods perceived as inefficient and time-consuming, especially in the complaint handling service. Whereas complaints services can be a forum for tourists or the surrounding community to contribute in providing complaints about the tourist attractions they visit. Therefore, researchers leverage technological advancements to design a web-based tourism complaint service information system for the relevant department. Using UML modeling method, CodeIgniter framework version 3, Bootstrap version 4.4.1, PHP programming language, HTML, CSS, JavaScript, and MySQL for database connectivity, this research aims to be implemented so that the department can efficiently manage complaint services and respond promptly.